Предмет: Алгебра,
автор: ladypashenko
(a + 3b)^2 - (3a + b)^2
Ответы
Автор ответа:
0
(a + 3b)² - (3a + b)²=a²+6ab+9b²-(9a²+6ab+b²)=a²+6ab+9b²-9a²-6ab-b²=8b²-8a²=8(b²-a²)=8(b-a)(b+a)
Автор ответа:
0
a²+6ab+b²-a²+6ab+b² = 12ab + 2b²
Автор ответа:
0
Надо ли выносить 2 b в квадрате .
Автор ответа:
0
хмммхм..
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Информатика,
автор: Аноним
Предмет: История,
автор: armansarscom
Предмет: Физика,
автор: Ninochca
Предмет: Физика,
автор: 1a2a3a4a5a6a7a8a9a